Instructional Design Applied by Teachers Affects Library Utilization - Ferrater-Gimena, Judy-Ann Ong; Doming, Roselita Rafols (JPAIR Institutional Research, 2014)
University libraries support the learning needs of students. Library resources and services are important tools for effective teaching and learning. However, there are various influences that affect the motivation of the university to use the library. The study assessed the level of awareness and extent of utilization of the library services and resources at the University of Cebu-Banilad as perceived by its faculty and students. The researcher was prodded to conduct the study because, at present, the utilization of the library services and resources is at a lower level compared to the ideal and the intended users of this academic facility were not even aware of the existence of the some of the library services. This research utilized the descriptive correlation design and used the researcher-made questionnaire as a tool of data collection. A total of 531 respondents comprised of 151 faculties and 380 students. It was concluded that the utilization of the library system as a whole was primarily influenced by varying factors. Foremost of these factors is instructional design utilized by the teacher.
Keywords: Library science; current awareness services; instructional design; library promotion; strategies; library resources; descriptive design; Cebu City; Philippines